Willow growth in response to nutrients and moisture on a clay landfill cap soil. II: Water use - Martin, Peter J.; Stephens, William (Elsevier, 2005)
This paper describes studies into the effects of soil factors and water stress on water use by willow (Salix viminalis L.) on a clay landfill cap soil and a sandy loam. Individual plants were grown in lysimeters containing these soils under different watering regimes and with different soil amendment treatments. Stemflow and throughfall were measured to determine rainfall entering the lysimeters and evapotranspiration (ET) calculated from a water balance. With plentiful water, seasonal ET increased annually in most treatments, reflecting increases in plant leaf area and dry matter production. For the most vigorous plants, in the sandy loam treatment, it increased from about 360 l plant-1 in the establishment year to almost 1200 l plant-1 in the third year. Seasonal ET was highly correlated with leaf area duration. Nutritional amendment of Oxford clay resulted in plants with larger leaf area and higher dry matter production and seasonal ET than in the unamended treatment. Water stress reduced seasonal ET by up to 41%, as a result of defoliation and stomatal closure. In unstressed plants, in the sandy loam treatment, daily ET rates per unit leaf area reached a maximum of about 1.5 l m-2 d-1 in July. Without nutritional amendment, water use efficiency (WUE) calculated from plant ET and root, stump and stem dry weight, was low for the unamended Oxford clay treatment (1.4 g kg-1) but was similar in the amended clay (5.0 g kg-1) and sandy loam (4.9 g kg-1) treatments. The study has shown the dependence of biomass production by willow on Oxford clay on both nutritional amendment and water availability. Although both nutrients and water could be supplied at these sites by growing SRC within a leachate management system, there are several practical issues like the narrow window of opportunity for mechanised operations and concerns about long-term sustainability which still need to be addressed.
Keywords: Canopy interception; Short-rotation coppice